Image quality assessment with dose reduction using high kVp and additional filtration for abdominal digital radiography. (June 2018) - Jang, Ji Sung; Yang, Hyung Jin; Koo, Hyun Jung; Kim, Sung Ho; Park, Chan Rok; Yoon, Suk Hwan; Shin, So Youn; Do, Kyung-Hyun
Highlights: Additional filtration and high kVp are effective methods for dose reduction. Use of 92 kVp and Cu filter can reduce effective dose with good image quality. Radiation exposure time is decreased by applying 92 kVp with 0.1 mm Cu filter. Abstract: Purpose: Dose reduction using additional filters with high kilovoltage peak (kVp) for abdominal digital radiography has received much attention recently. We evaluated image quality with dose reduction in abdominal digital radiography by using high kVp and additional copper filters at a tertiary hospital. Methods: Between June 2016 and July 2016, 82 patients underwent abdominal digital radiography using 80 kVp in X-ray room 1 and 82 were imaged using 92 kVp with 0.1-mm copper filtration in X-ray room 2. The effective dose was calculated using a PC-based Monte Carlo program. Image quality of the abdominal radiography acquired in the two rooms was evaluated using a five-point ordinal scale, as well as the signal-to-noise and contrast-to-noise ratios. Results: The mean effective dose decreased by 25.8% and 25.7% for the supine and standing positions, respectively, when abdominal digital radiography using 92 kVp with 0.1-mm copper filtration was performed. In the 20 patients who performed abdominal digital radiography twice in each room, visual grading scores for visualisation of psoas outlines and kidney outlines are higher in room 1. However, there was no statistical significant difference of visual grading scores among the 124 patients who underwent only one abdominal radiography in the room 1 or 2 ( P  > 0.05). Conclusions: Dose reduction for abdominal digital radiography can be achieved with comparable image quality by performing abdominal digital radiography using 92 kVp with 0.1-mm copper filtration, despite the higher AEC dose.